2016
DOI: 10.1158/0008-5472.can-15-1090
|View full text |Cite
|
Sign up to set email alerts
|

A Preclinical Model of Malignant Peripheral Nerve Sheath Tumor-like Melanoma Is Characterized by Infiltrating Mast Cells

Abstract: Human melanomas exhibit considerable genetic, pathologic, and microenvironmental heterogeneity. Genetically engineered mice have successfully been used to model the genomic aberrations contributing to melanoma pathogenesis, but their ability to recapitulate the phenotypic variability of human disease and the complex interactions with the immune system have not been addressed. Here, we report the unexpected finding that immune cell-poor pigmented and immune cell-rich amelanotic melanomas developed simultaneousl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 50 publications
(46 reference statements)
3
24
0
Order By: Relevance
“…There are certain tumors such as breast cancer (106, 107, 109) in which mast cells always appear to play an antitumorigenic role. The role of mast cells in the pathogenesis of human melanomas is still unclear and appears to depend on both the microlocalization of these cells (43) and the subtypes of tumor (83). …”
Section: The Contribution Of Mast Cells To Cancer Is Tumor Dependentmentioning
confidence: 99%
See 2 more Smart Citations
“…There are certain tumors such as breast cancer (106, 107, 109) in which mast cells always appear to play an antitumorigenic role. The role of mast cells in the pathogenesis of human melanomas is still unclear and appears to depend on both the microlocalization of these cells (43) and the subtypes of tumor (83). …”
Section: The Contribution Of Mast Cells To Cancer Is Tumor Dependentmentioning
confidence: 99%
“…There is increasing evidence that different stages of tumors can be associated with qualitative and quantitative changes in different types of immune cells in the periphery and center of tumors (146, 147). The pro- or antitumorigenic role of mast cells in different types of melanomas remains controversial (83, 148). Siiskonen and collaborators found that tryptase + chymase + mast cells in perilesional stroma of melanoma play a protective role (43).…”
Section: The Role Of Mast Cells In Tumors Varies According To Their Mmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, in breast cancer mast cells appear to play an anti‐tumorigenic role. The role of mast cells in the pathogenesis of human melanomas is still unclear and depends on both the microlocalization of these cells and the subtypes of tumor . These results suggest that the contribution of mast cells to cancer is tumor dependent.…”
Section: Role Of Mast Cells and Basophils In Health And Diseasementioning
confidence: 99%
“…In the case of melanoma, there is substantial documentation from both clinical studies and from animal models supporting that MCs participate in this pathology [1422] (reviewed in [12]). However, there is still only little knowledge of the mechanism(s) by which MCs contribute to this malignancy.…”
Section: Introductionmentioning
confidence: 99%